Evaluación del desarrollo vegetativo de plántulas de banano (musa spp.) var. williams con propagación a partir de yemas adventicias utilizando dos sustratos y dos biorreguladores de crecimiento - Flores Merizalde, Frixon Ricardo (2022)
The present investigation was carried out in the Chipe Hamburgo 2 sector, of the El Triunfo parish, belonging to the La Maná canton, with the following objectives: Analyze the variables of growth and agronomic development of banana seedlings multiplied from adventitious buds, establish the best substrate and biostimulant in the production of banana seedlings under nursery conditions and to determine the effect of the substrates in combination with biostimulants on the development of banana seedlings. A Completely Random Design was used using a factorial arrangement formed by 2 types of substrates and 2 growth bioregulators, resulting in 4 treatments with an absolute control, each treatment consisted of 4 repetitions. The following variables were analyzed: days to bud emission, plant height, pseudostem diameter, number of leaves, slenderness coefficient, number of roots and root length. The results with fewer days to the emission of buds were obtained with T2 (rice husk substrate + cytokinin) with 6.50 days from the sowing of buds, at the highest plant height T2 (rice husk substrate + cytokinin) obtained the best results at 30, 45 and 60 days with data of 21.79, 31.57 and 35.22 cm respectively, for the diameter of pseudostem T2 (rice husk substrate+ cytokinin) obtained the highest values with 3.74, 4.23 and 6.30 cm in all the ages evaluated, in the number of leaves T2 (substrate rice husk + cytokinin) showed more number of leaves in the registered ages with results of 4.25, 6.25 and 6.75 leaves per plant, the slenderness coefficient with acceptable values was presented in T2 (rice husk substrate + cytokinin) with an index of 5.27, while in the variable number of roots T3 (rice husk substrate + cytokinin) is presented as the best treatment with 23.63 root. Finally, in the length of roots T2 (substrate rice husk + cytokinin) was the one that presented the longest roots with 27.88 cm.